Beach safety education for primary school children. Issue 3 (3rd July 2017) - Wilks, Jeff; Kanasa, Harry; Pendergast, Donna; Clark, Ken
Abstract : Childhood drowning remains a serious public health problem worldwide. The Australian Water Safety Council has set as one of its highest priorities the reduction of drowning deaths in children aged 0–14 years. However, concerns have recently been raised that many students completing primary school still lack the ability to recognize potential aquatic risks, cope with emergencies or assist someone else in danger. In this study, 107 primary school children aged 11–12 completed a one day training programme led by surf lifesaving instructors. Pre, post and eight week follow-up measures showed statistically significant improvements in recognition of the red 'beach closed' flag, aquatic safety signs, how to identify a rip current and choosing the safest place to swim at a beach that included a rip current in the picture. Following training students were more willing to provide first aid assistance to family members and friends in an emergency situation. Findings reinforce the value of school-based training that provides a general foundation for aquatic safety, with the caveat that current programmes must be evaluated to ensure their content has a robust prevention focus.